Mother–child conversation and social understanding in Pakistan. (September 2018) - Nawaz, Sumbal; Lewis, Charlie
Two studies are presented to examine whether and why 3–5-year-olds in Pakistan display limited social understanding. Study 1 tested 71 preschoolers on Lillard and Flavell's (1992) test of desires, pretence and beliefs, plus two false belief tasks, and showed very limited understanding across these measures even though almost half were over 5 years old. Study 2 replicated this effect with 35 preschoolers, and also conducted home observations of mother–child interaction at two time points. It tested three competing explanations of the role of adult-conversation in the preschooler's developing understanding of the mind: the quality of the caregiver's references to mental states, the child's grasp of mental state language in such conversations, and the connectedness of adult–child talk. These factors are usually highly correlated in Western cultures. In Pakistan, with a delay in the acquisition of social understanding skills, Study 2 showed that maternal and child references to mental states were rare (2% of maternal and 1% of child utterances). Analyses of the relationship between mother–child conversation and the children's test performance suggested that the measures of social understanding were not predicted uniquely by the connectedness of talk within the dyad, or maternal use of mental state terms. However, the children's concurrent (and to a lesser extent previous) use of mental state terms was related to their grasp of mental states. Thus, the data support previous analyses, which suggests that the child's construction of mental state terms is more crucial in their grasp of the social world.